2022
DOI: 10.1155/2022/8153521
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Physical Function of Shuttlecock Players after Short-Term Intensive Training based on Data Mining

Abstract: This paper investigates the changes in body composition and physical fitness of badminton players after short-term high-intensity training. Methods. During an 8-week short-term training camp, 12 nonprofessional badminton players were paired to design training sessions, and body composition and fitness were measured before and after training. Results. After 8 weeks of high-intensity training, there was no significant change in body weight of badminton players … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The game of shuttlecock, often called kicking shuttlecock, is well-known and has a lengthy history. Regular shuttlecock practice may improve a player (Zeng, 2022). The sport of shuttlecock, which originated in China, has a remarkable and significant place in traditional Vietnamese gymnasiums.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The game of shuttlecock, often called kicking shuttlecock, is well-known and has a lengthy history. Regular shuttlecock practice may improve a player (Zeng, 2022). The sport of shuttlecock, which originated in China, has a remarkable and significant place in traditional Vietnamese gymnasiums.…”
Section: Introductionmentioning
confidence: 99%
“…It has been developed for many years in China. The shuttlecock tournament was staged for the first time in December 1928 in Shanghai during the "China Domestic Products Exhibition," which aided in the project's advancement (Zeng, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%